A Decade of Cave Drip Hydrographs Shows Spatial and Temporal Variability in Epikarst Storage and Recharge to Appalachian Karst Systems - Nigel C. Groce-Wright; Joshua R. Benton; Nicholas W. Hammond; Madeline E. Schreiber (Hydrology, 2022)
We conducted recession analyses on cave drip hydrographs from a 10-year record (2008–2018) of three drip monitoring stations within James Cave (Pulaski County, VA, USA) to examine differences in hydrologic characteristics of the epikarst and quantify the storage volume of the epikarst feeding the drips. We used two recession analysis methods (correlation and matching strip) to calculate recession coefficients for multiple hydrographs at each site. Results show subtle differences between the three drip sites, suggestive of spatial heterogeneity in permeability and storage in the overlying epikarst. Storage volume calculations show that during the recharge season, up to 95% of recharge through the epikarst to the cave occurs through rapid pathways (i.e., fractures), and 5% of recharge occurs through diffuse pathways (i.e., pores). However, during the recession period, recharge through rapid pathways in the epikarst decreases and occurs predominantly through diffuse flow. Combined, these results underscore the importance of documenting spatial and temporal characterization of drip rates and other recharge inputs into karst systems.